A interação sociodiscursiva entre professor-autor e revisor de textos na produção de material didático impresso para EAD - Diniz, Raquel Ribeiro (2017)
One of the possible forms of interaction in distance education (DE) occurs through printed didactic material (PDM), which acts as a link between student and content, supplying the teacher’s physical absence. Once it has diversified dynamics and characteristics compared to the material for face-to-face teaching and because it is often the only source of study to which the student has access, it is necessary that the PDM for DE be planned, developed and applied respecting the specificities that the modality requires and also with the purpose of facilitating the comprehention of the content by the student. Thus, special attention should be given to the production process, which is organized in stages with different activities and different agents, among them the teacher-author, responsible for the preparation of the text, and the reviewer, in charge of the revision of this text. The interaction between these two subjects is the theme of the present work, once it is carried out, discursively, in the materiality of the text, through the activities of writing, revision and textual rewriting. Thus, the general objective of this research is to investigate how the student is involved in the interaction between the reviewer of texts and teacher-author in the production process of the PDM from the Licentiate Letters Course in Distance Learning at Federal Institute of Education, Science and Technology from Paraíba. For that, 108 excerpts were analyzed (half composed by the original texts of the teacher-author with the interventions of the reviewer and half by the rewritten texts postintervention) that are part of 29 lessons of 11 curricular components, referring to the first two periods of the course, reviewed by three reviewers. This research, inserted in the Applied Linguistics area, has a qualitative-interpretative character and uses documentary corpus. For data analysis, the interventions of the reviewer were classified according to the typology of Serafini (1994) and Ruiz (2001). In addition, the research was based on the theoretical postulates of the Sociodiscursive Interactionism, mainly related to the production conditions of the PDM from Letters Course (BRONCKART, 1999), to the characterization of this material as textual genre (BAKHTIN, 2000; BRONCKART, 1999; VOLOCHINOV, 2014), to the concept of language action and the capacities that are mobilized in it (BRONCKART, 1999, 2006, 2008; CRISTOVÃO, 2007; SCHNEUWLY; DOLZ, 2004). Among the results, it is emphasized that the intervention of the reviewer is not a purely objective activity, because this professional, in and by the language, constitutes him/herself as subject and does not act, simply, in the sphere of the language, once the revision goes beyond the simple hygiene of the text and has a discursive nature. The review is made considering the physical and sociosubjective production context of the text and the textual genre; it focuses the text in its full dimension, encompassing the different language abilities. And the sociodiscursive interaction that occurs between reviewer and teacher-author contributes so that the PDM can fulfill its pedagogical purposes too and, consequently, contemplate the student’s teaching and learning process, once the student is involved in this interaction.